A graph theoretical model for the total balancedness of combinatorial optimization games - Escalante, Mariana Silvina (2012)
In this paper we present a model for the study of the total balancedness of packing and covering games, concerning some aspects of graph theory. We give an alternative proof of van Velzen’s characterization of totally balanced covering games. We introduce new types of graph perfection, which allows us to give another approach to the open problem of characterizing totally balanced packing games.